Implantation of Heparin-Conjugated Fibrin Hydrogel for Local Defects of Cartilage in Knee Osteoarthritis: A Case Report - Toktarov T; Raimagambetov Y; Balbossynov B; Saginova D; Abilmazhinov M; Ogay V (International Medical Case Reports Journal)
Tusipkhan Toktarov,1,2 Yerik Raimagambetov,1 Bagdat Balbossynov,1 Dina Saginova,1 Mukhtar Abilmazhinov,2 Vyacheslav Ogay1,3 1National Scientific Center of Traumatology and Orthopedics Named After Academician Batpenov N.D., Astana, Kazakhstan; 2Astana Medical University, Astana, Kazakhstan; 3Stem Cell Laboratory, National Center for Biotechnology, Astana, KazakhstanCorrespondence: Tusipkhan Toktarov, Astana Medical University, Beybitshilik 49 A, Astana, Z10K8Y7, Kazakhstan, Tel +77052928127, Email toktarov.tusya@gmail.comBackground: Cartilage defects in the knee joint are areas of damage and wear to the cartilage that normally covers and protects the ends of bones. These defects occur due to sudden injuries, such as trauma or sports accidents, or due to chronic conditions, such as osteoarthritis. Cartilage acts as a shock absorber (cushion absorber), reducing the impact of mechanical stress on the joints, which helps prevent bone damage during movement. Cartilage also serves as a gliding surface for the joints, allowing them to move smoothly, which minimizes friction between the bones. Its damage can cause pain, swelling, and decreased joint function. Treatment of localized cartilage defects is important to prevent further damage to the joint and maintain good knee function. Identifying problems early and treating them correctly can help improve outcomes and reduce the likelihood of more serious joint problems.Case Description: We describe the case of a 46-year-old man with a localized cartilage defect in the knee joint who was followed for one year after the application of heparin-conjugated fibrin hydrogel for the treatment. We watched the patient for a year, doing functional tests, checking MRI results after the procedure, and watching for side effects.Results: This case demonstrates that implantation of hydrogel successfully engraft and lead to remodeling of hyaline-like cartilage, thereby improving the condition of damaged knee cartilage. Comparison of MRI images before and 1 year after surgery showed the effectiveness of this technology.Keywords: cartilage defects, knee joint, mesenchymal stem cells, fibrin hydrogel, growth factors